Politics and the life sciences the state of the discipline - Stewart, Patrick (Emerald, 2014)
This book examines the development of biopolitics as an academic perspective within political science. It reviews the work of the leading proponents of this perspective and presents a comprehensive view of biopolitics as a framework to structure political inquiry. The book's chapters present a range of analysis, critique and recommendations for the current study of biopolitics. Coverage includes; the implications of biopolitics for political theory and the need to re-evaluate basic assumptions of the prevailing political science paradigm; an analysis of the methodological concerns of adopting a more biology-based approach to political science; the current state of knowledge of the genetic and neurological bases of mass and elite behavior; and biopolicy issues and the proper role of the life sciences in informing our understanding of them. The concluding chapter restates the case for a paradigm shift toward an interactive model, arguing that, rather than lead to biological determinism as denounced by some, this inclusive paradigm allows us to counteract deterministic protestations more effectively than by continuing to ignore or minimize biological influences.
Keywords: Political Science -- General.; Social Science -- Gender Studies.; Political science & theory.; Gender studies, gender groups.; Biopolitics.; elektronické knihy; electronic books